Protein Farnesylation Takes Part in Arabidopsis Seed Development - Vergès, Valentin; Dutilleul, Christelle; Godin, Béatrice; Collet, Boris; Lecureuil, Alain; Rajjou, Loïc; Guimaraes, Cyrille; Pinault, Michelle; Chevalier, Stéphane; Giglioli-Guivarc’h, Nathalie; Ducos, Eric (Frontiers in Plant Science, 2021)
Protein farnesylation is a post-translational modification that regulated by the ERA1 (Enhanced Response to ABA 1) gene encoding the β-subunit of the protein farnesyltransferase in Arabidopsis. The era1 mutants have been described for over two decades and exhibits severe pleiotropic phenotypes, affecting vegetative and flower development. We further investigated the development and quality of era1 seeds. While the era1 ovary contains numerous ovules, the plant produces fewer seeds but larger and heavier, with higher protein contents and a modified fatty acid distribution. Furthermore, era1 pollen grains show lower germination rates and, at flower opening, the pistils are immature and the ovules require one additional day to complete the embryo sac. Hand pollinated flowers confirmed that pollination is a major obstacle to era1 seed phenotypes, and a near wild-type seed morphology was thus restored. Still, era1 seeds conserved peculiar storage protein contents and altered fatty acid distributions. The multiplicity of era1 phenotypes reflects the diversity of proteins targeted by the farnesyltransferase. Our work highlights the involvement of protein farnesylation in seed development and in the control of traits of agronomic interest.